A low-cost and efficient solar/coal hybrid power generation mode: Integration of non-concentrating solar energy and air preheating process. (15th November 2021) - Han, Yu; Sun, Yingying; Wu, Junjie
Abstract: Solar-aided power generation (SAPG) is an effective method for achieving clean and efficient production of electricity. The unique characteristics of the non-concentrating solar energy and air preheating process open up a novel method for low-cost and efficient solar/coal hybrid power generation. In the proposed novel SAPG, non-concentrating solar energy achieves high solar-to-electricity efficiency by efficiently integrating it with the air preheating process. Additionally, the new system generates electricity at a low cost by applying non-concentrating solar collectors. The results reveal that based on a typical 1000 MW coal-fired power plant, the proposed SAPG generates 12.6 MWe of additional output power with a 0.57% increase in coal-based thermal efficiency, and reduces the exergy loss during the air preheating process by 36.6%. Owing to the low cost and efficient utilization of non-concentrating solar energy, the cost of solar-generated electricity of the proposed SAPG is only 47.4% of that of the conventional SAPG. The high thermal and economic performance of the proposed SAPG opens up a low-cost and efficient solar/coal hybrid power generation mode through the integration of non-concentrating solar energy and air preheating process. Graphical abstract: Image 1 Highlights: A low-cost and efficient solar/coal hybrid power generation mode is proposed. Non-concentrating solar energy is integrated with air preheating process. The proposed SAPG achieves a solar-to-electricity efficiency of 27.5%. The cost of solar generated electricity is 0.048 USD/kWh. The proposed SAPG keeps high performance in off-design conditions.